2018
DOI: 10.1016/j.cmi.2018.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine kinetic profiles in children with acute lower respiratory tract infection: a post hoc descriptive analysis from a randomized control trial

Abstract: We observed an earlier decrease of elevated cytokines compared to PCT or CRP. Both pro- and anti-inflammatory cytokines may serve as markers for severity of LRTI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Host-response biomarkers, such as C-reactive protein, interleukin(IL)-6, and procalcitonin, have been increasingly used to assist the diagnosis of a variety of infectious diseases, including pneumonia and sepsis. [66][67][68][69][70][71] A meta-analysis of 6708 adults with acute respiratory infection found that the use of procalcitonin to guide therapy was associated with a 17% reduced risk of mortality and a 2·4-day reduction in antibiotic exposure compared with controls, without increasing adverse outcomes. 72 However, data in children are scarce, and early studies have conflicting results.…”
Section: Host-response Biomarker Testingmentioning
confidence: 99%
“…Host-response biomarkers, such as C-reactive protein, interleukin(IL)-6, and procalcitonin, have been increasingly used to assist the diagnosis of a variety of infectious diseases, including pneumonia and sepsis. [66][67][68][69][70][71] A meta-analysis of 6708 adults with acute respiratory infection found that the use of procalcitonin to guide therapy was associated with a 17% reduced risk of mortality and a 2·4-day reduction in antibiotic exposure compared with controls, without increasing adverse outcomes. 72 However, data in children are scarce, and early studies have conflicting results.…”
Section: Host-response Biomarker Testingmentioning
confidence: 99%
“…Among host factors, cytokines are known to play important antiviral roles, but they may also cause damage to respiratory tract and lung 11,12 . Therefore, the balance between pro-inflammatory and anti-inflammatory cytokines determines the outcome of an immune response to an infection.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that persistent chronic inflammation will damage the development of airway and lung tissues, leading to subsequent respiratory diseases such as asthma 11,1315 . To date, only a limited number of studies investigate cytokine profiles in children with ARTIs, mostly in relation to specific respiratory virus infection (e.g., influenza, rhinovirus) 11,12,16 . No studies are designed to measure cytokine profiles longitudinally among children with multiple ARTIs.…”
Section: Introductionmentioning
confidence: 99%
“…It can be secreted by almost all stromal cells and cells of the immune system at an early stage of in ammation (with rapid elevation in 1-3 hours), and further promote the synthesis and release of CRP by the liver [21,22]. IL-6 has been previously described as a marker of different types of SBI (alone or in combination with other biomarkers) [23,24] such as early-onset neonatal sepsis [25,26], sepsis and septic shock [21,23,27] bacteremia in patients with febrile neutropenia [28,29] or pneumococcal pneumonia [30][31][32][33]. The early elevation of IL-6 that occurs in the presence of SBI is an important advantage of this cytokine over other biomarkers.…”
Section: Discussionmentioning
confidence: 99%